Electrochemical Performances of Electroactive Nano-LayeredOrganic-Inorganic Perovskite Containing Trivalent Iron Ion and its Use for a DNA Biosensor Preparation. (29th June 2010) - Wu, Jing; Liu, Hanxing; Lin, Zhidong; Cao, Minghe
Abstract : A steady nano organic-inorganic perovskite hybrid with [ H 2 3 -AMP ] 3 / 2 Fe(CN)6 (3-AMP = 3-methylaminopyridine) was prepared in the air. The structure is an unusual layered organic-inorganic type. The resulting hybrid enveloped in paraffin to prepare [ H 2 3 -AMP ] 3 / 2 Fe(CN)6 paste electrode (HPE) shows good electrochemical activity and a couple of oxidation and reduction peaks with potential of cyclic voltammometry (CV) at around 440 mV and 30 mV. Compared with that on CPE, oxidation potential of F e ( C N ) 6 3 - on HPE shifts negatively 259.7 mV and that of reduction shifts positively 338.7 mV, which exhibits that [ H 2 3 -AMP ] 3 / 2 Fe(CN)6 can accelerate the electron-transfer to improve the electrochemical reaction reversibility. Such characteristics of [ H 2 3 -AMP ] 3 / 2 Fe(CN)6 have been employed to prepare the DNA biosensor. The single-strand DNA (ssDNA) and double-strand DNA (dsDNA) immobilized on HPE, respectively, can improve the square wave voltammometry (SWV) current and SWV potential shifts positively. The effect of pH was evaluated. And there is hybridization peak on SWV curve using HPE immobilized ssDNA in the complementary ssDNA solution. And HPE immobilized ssDNA can be utilized to monitor the DNA hybridization and detect complementary ssDNA, covering range from 3.24 × 10 − 7 to 6.72 × 10 − 5  g/mL with detection limit of 1.57 × 10 − 7  g/mL. The DNA biosensor exhibits a good stability and reproducibility.